Subacromial impingement in front-crawl swimming: a preliminary report - Du, T.; Yanai, T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purposes of the present study were to measure the glenohumeral joint motion exhibited during front-crawl swimming and to re-examine the instances at which the subacromial structures were experiencing impingement. A series of glenohumeral configurations indicative the impingement were measured to define the so called "boundary range of motion," which was used to identify if the glenohumeral configurations exhibited at any instant during swimming is indicative of impingement. A simplified kinematic model composed of right scapula, right humerus and thorax was used to describe the shoulder configuration for three collegiate swimmers. The results showed that impingement occurred for 0~ 12% of the stroke time during the front-crawl for the three subjects.